Science Education Research and Practice in Europe Retrosspective and Prospecctive - Jorde, Doris; Dillon, Justin; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Each volume in the 7-volume series The World of Science Education reviews research in a key region of the world. These regions include North America, South and Latin America, Asia, Australia and New Zealand, Europe, Arab States, and Sub-Saharan Africa. The focus of this Handbook is on science education in Europe. In producing this volume the editors have invited a range of authors to describe their research in the context of developments in the continent and further afield. In reading this book you are invited to consider the historical, social and political contexts that have driven developments in science education research over the years. A unique feature of science education in Europe is the impact of the European Union on research and development over many years. A growing number of multi-national projects have contributed to the establishment of a community of researchers increasingly accepting of methodological diversity. That is not to say that Europe is moving towards homogeneity, as this volume clearly shows.
Keywords: Education; Education; Education (general).